2012 IEEE International Symposium on Information Theory Proceedings 2012
DOI: 10.1109/isit.2012.6284026
|View full text |Cite
|
Sign up to set email alerts
|

Codes can reduce queueing delay in data centers

Abstract: Abstract-In this paper, we quantify how much codes can reduce the data retrieval latency in storage systems. By combining a simple linear code with a novel request scheduling algorithm, which we call Blocking-one Scheduling (BoS), we show analytically that it is possible to reduce data retrieval delay by up to 17% over currently popular replication-based strategies. Although in this work we focus on a simplified setting where the storage system stores a single content, the methodology developed can be applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(152 citation statements)
references
References 11 publications
(16 reference statements)
5
147
0
Order By: Relevance
“…Related design can also be found in data access scheduling [14,16,19,20], access collision avoidance [17,18], and encoding/decoding time optimization [32,33] and there are also some work using the LT erasure codes to adjust the system to meet user requirements such as availability, integrity and confidentiality [6]. Restricting to the special case of a single file or homogeneous files, service delay bounds of erasure-coded storage have been recently studied in [40,45,49,50]. Queuing-theoretic analysis.…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Related design can also be found in data access scheduling [14,16,19,20], access collision avoidance [17,18], and encoding/decoding time optimization [32,33] and there are also some work using the LT erasure codes to adjust the system to meet user requirements such as availability, integrity and confidentiality [6]. Restricting to the special case of a single file or homogeneous files, service delay bounds of erasure-coded storage have been recently studied in [40,45,49,50]. Queuing-theoretic analysis.…”
Section: B Related Workmentioning
confidence: 99%
“…For a single file or multiple but homogeneous files, under an assumption of exponential service time distribution, the authors in [5] proved an asymptotic result for symmetric large-scale systems which can be applied to provide a computable approximation for expected latency, however, under a assumption that chunk placement is fixed and so is coding policy for all requests, which is not the case in reality. Also, the authors in [40,45] proposed a block-onescheduling policy that only allows the request at the head of the buffer to move forward. An upper bound on the average latency of the storage system is provided through queuingtheoretic analysis for MDS codes with k = 2.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…$15.00 DOI: 10.1145/nnnnnnn.nnnnnnn simultaneously download from di erent replicas, or each user can issue simultaneous requests to multiple replicas and wait for the rst download to nish [6,7,15]. Data access systems arising in erasure coded storage have received a lot of a ention for all-data (see for example [12,14,19,24] and references therein) and some for hot-data download [16,17], and usually involve single or multiple inter-dependent fork-join queueing systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [4], latency delay was reduced by choosing MDS codes of appropriate rates. Latency comparison between a simple replication scheme and MDS codes was pioneered by Huang et al [5] using queuing theory. It was shown that for k = 2, the average latency for serving a packet decreases significantly when a certain scheduling model is used.…”
Section: Introductionmentioning
confidence: 99%